The Use Of Advanced Bibliometric Analysis In Research Performance Assessment And Monitoring At Universiti Malaysia Terengganu - Harisom Anida Binti Musa (Universiti Malaysia Terengganu, 2022)
Institutions of higher learning worldwide are involved with the world-class university ranking and rating system because it is believed to represent the academic excellence and reputation of the institution. In most university rankings such as Times Higher Education (THE) and QS World University Ranking, research output is one of the important criteria used in making the ranking assessment. Quality of academic programs, research and publication has been at the forefront of the debate on measuring the performance of universities. Realizing that the value of publishing can affect the rating system, then an institution of higher learning uses publication information or bibliometric analysis as an indicator to evaluate the contribution and rating of the institution. The research project therefore provides an overview of advanced bibliometric methods for the assessment of research performances at UMT and for monitoring interdisciplinary scientific development. The study employed a query search on the Universiti Malaysia Terengganu affiliation using Scopus and WoS database for a comprehensive research performance overview within year 2015-2019. Results shown, the massive increment volume of publication among UMT researcher with number of publications 3805 and was publish highest in journal WoS -Q1 (29%) and Scopus - Q2 (25%). Universiti Kebangsaan Malaysia (UKM) is the highest national and institutional collaborating with UMT.